The Computer-mediated Living Group, Microsoft Research Cambridge - Sellen, Abigail; Banks, Richard; Harper, Richard; Hodges, Steve (Interactions Magazine, 2014)
We aim to build new technologies, map out new design spaces, and provide different ways of looking at human behavior.